Chinese gardens - Lou, Qingxi ([Beijing] : China Intercontinental Press, 2003)
A history of Chinese gardens that discusses the art and architecture of the gardens and how the theories of Chinese garden design have evolved through the years. Includes black-and-white and color photographs.
Translation of: Zhongguo yuan lin.
Adult
Keywords: Chinese gardens -- China; Gardens, Chinese -- China